SENTRALISASI ISLAM MARJINAL: Konstruksi Pemikiran Hamka dalam Historiografi Islam Melayu-Nusantara - Lukmanul Hakim (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
This paper aims to analyze the thoughts of Hamka in Malay Islamic Nysties Historiography. The method used is historical method, especially historiography approach. Characteristic of Hamka's work; First, writing techniques; Not using footnotes, style of language; Simple, alive, and communicative. The sources used by Hamka can be grouped into three groups; Primary sources, historical books composed by Muslim authors themselves; Second, the second source of material is the Dutch and British writers' writings on Indonesia and the Malay Land; Third, the third source of material materials that allegedly most of the writers of Islamic history in Indonesia did not get it. While from the Method of Historical Criticism, according to Hamka there are two ways to write history among Muslims; First collecting all the facts wherever it comes from, no matter whether the facts make sense or not, what needs to be taken care of is where this history is received. Second, judging the facts and giving their own opinions, after the facts were collected, this is the system used by Ibn Khaldun.